Analysis on the form of conclusive writing in scientific articles in the field of Agrarian Sciences (Research, Society and Development, 2021)
Conclusion is the last textual element in a scientific paper; Its presentation form, however, is not yet standardized among the publications of scientific journals. The objective of this research was to carry out an analysis on the form of the conclusive writing in national scientific articles, based on 40 periodicals of the area of ​​agrarian sciences, published in the period 2003-2017. The analyzed indicators were: forms (synonyms) of the writing of Conclusion; Type of signal used before each conclusion; Number of conclusions; Style of the Conclusion; Verb tense used in the concluding paragraphs; Presence of personifying expressions; and presence of the object of study in the concluding paragraphs. The results show that the expression CONCLUSIONS (plural and upper case) is the most used (32.507%) among the analyzed journals; Simple paragraph (without number or symbol) is predominant (70%); 45% of the articles present 2 (two) specific conclusions; 70% of the articles only show Conclusion (without additional information); The “present” tense is the most used form in the concluding paragraphs (40%); conclusions are written impersonally (100%); and the presence of the object of study (in all articles: crops) in the concluding paragraphs is more prevalent through vulgar nomenclature (62.50%). It is concluded that the diverse form of presentation of the conclusive paragraphs in national scientific articles, in the area of ​​agriculture sciences, deserves special attention in the search for a model that allows narrowing its multiple form in order to achieve a more functional writing.